The worst night ever - Barry, Dave (Disney/Hyperion, 2016)
Now that Wyatt Palmer, former middle school hero, has entered high school, he's just another underclassman trying to fit in, or at least not stand out in a bad way. But when is best friend, Matt, brings his ferret, Frank, to school, the most popular boys in school, the Bevin brothers, get their hands on Frank. And when Wyatt and Matt set out to get Frank back, they stumble onto some dark and deadly secrets that make being popular the least of their worries.